Serologic Evidence of Brucella Spp. Exposure in Atlantic Walruses (Odobenus Rosmarus Rosmarus) and Ringed Seals (Phoca Hispida) of Arctic Canada - Nielsen, Ole; Nielsen, Klaus; Stewart, Robert E.A. (ARCTIC, 1996)
The first presumptive evidence of Brucella infection in marine mammals of Arctic Canada is reported. Blood samples were collected from 248 ringed seals (Phoca hispida) and 59 Atlantic walrus (Odobenus rosmarus rosmarus) from eight locations in the Canadian Arctic between 1987 and 1994. A competitive enzyme-linked immunosorbent assay (C-ELISA), using a specific monoclonal antibody to Brucella spp. cell wall components, was used to detect anti-Brucella spp. antibodies in the samples. Sera from ten seals and seven walruses exceeded the C-ELISA threshold that indicates that cattle have been exposed to Brucella spp. Five of the positive walrus sera were suitable for the tube agglutination test. All five were confirmed positive using this test. Although the bacterium has not yet been identified, it appears that a Brucella sp. or a Brucella-like bacterium may be enzootic in these species in the Canadian Arctic. It is also possible that the very low prevalence of antibodies in ringed seals and the seemingly random distribution of seropositive animals may indicate a sporadic infection from another enzootically infected phocid or predator (e.g., Arctic fox Alopex lagopus). Or perhaps, limited epizootics may have occurred in the areas where seropositive seals were found. A similar situation could also exist in the walrus of Foxe Basin. On rapporte la première preuve par inférence d'une infection des mammifères marins de l'Arctique canadien par le bacille Brucella. Entre 1987 et 1994, on a effectué des prélèvements sanguins sur 248 phoques annelés (Phoca hispida) et 59 morses de l'Atlantique (Odobenus rosmarus rosmarus) à huit endroits dans l'Arctique canadien. On a employé la technique immuno-enzymatique par compétition ÉLISA, en se servant d'un anticorps monoclonal spécifique aux composants de la paroi cellulaire de Brucella spp, afin de détecter les anticorps anti-Brucella sp dans les prélèvements. Les sérums de dix phoques et de sept morses dépassaient le seuil d'ÉLISA qui indique que la population animale a été ...